Foreign languages in the Faculty of Education Sciences at the National University of Entre Ríos, Argentina (1984-2018) (Itinerarios Educativos, 2022)
This article focuses on the main aspects of a thesis work for a Master Degree in University Teaching granted by the Faculty of Education Sciences at the National University of Entre Ríos, Argentina. We introduce some initial questions about foreign language —French and English— teaching at the faculty along with the thesis topic and objectives. Afterwards, the tenets and practical aspects of the methodological approach are highlighted. And, finally, we explore the relationship between the curricula and the syllabi to draw some conclusions about the nature of the decision-making process in foreign language teaching at university.
Keywords: foreign languages; curricula; language teaching; university